2020
DOI: 10.5334/ijic.4649
|View full text |Cite
|
Sign up to set email alerts
|

Financial Barriers Decrease Benefits of Interprofessional Collaboration within Integrated Care Programs: Results of a Nationwide Survey

Abstract: Introduction: Interprofessional collaboration (IPC) is a key ingredient of integrated care. Nevertheless, IPC benefits remain unclear and its implementation within integrated care initiatives is not straightforward. In this study, we first explored whether IPC was associated with organisational and patient care improvements in Swiss integrated care initiatives; we then investigated the effect of various barriers faced by these initiatives, on these associations. Methods: Self-reported data from 153 integrated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 38 publications
0
13
0
Order By: Relevance
“…The difficulties encountered in developing and implementing interprofessional collaborative teams relate to a number of barriers encountered in clinical settings, including the structure of health care systems, which often makes smooth communication difficult. This can be exacerbated by financial constraints, regulatory processes and concerns about medico-legal issues (Gilles et al 2020;Lahey and Currie 2005).…”
Section: Interprofessional Coordinated Person/family Centred Carementioning
confidence: 99%
“…The difficulties encountered in developing and implementing interprofessional collaborative teams relate to a number of barriers encountered in clinical settings, including the structure of health care systems, which often makes smooth communication difficult. This can be exacerbated by financial constraints, regulatory processes and concerns about medico-legal issues (Gilles et al 2020;Lahey and Currie 2005).…”
Section: Interprofessional Coordinated Person/family Centred Carementioning
confidence: 99%
“…53 We found HCP needed more human resources to intensively support parents and the changes in IPC, and they thought it might be difficult to implement the model so it is financially sustainable. A recent Swiss study 13 found that financial barriers hindered IPC within integrated care. The current reimbursement system is not designed for integrated care and serves as a macro level barrier.…”
Section: Health Economic Barriersmentioning
confidence: 99%
“…The model adheres to principles of integrated care, including interventions and processes to improve interprofessional collaboration between stakeholders in the health care system and ensure that treatment and care of patients is coordinated optimally along the treatment continuum. 13 The "Transition to Home (TtH)" model is designed to optimize transitional care of families with preterm infants between 24 and 35 weeks of gestational age by giving parents and infants structured, individual support, improving parental mental health and competence, promoting the child's development, and optimizing interprofessional collaboration (IPC). This model is based on a German model that supports the families of chronically and severely ill children 14 and on Naylor's "Transitional Care Model" for hospitalized elders, 15 which was developed in the US.…”
Section: Introductionmentioning
confidence: 99%
“…Secondary data analyses of this national IC survey explored the influences of organisation and the funding of care on the implementation of interprofessional collaboration. Findings suggested that financial barriers hindered the association of interprofessional collaboration and organisational improvements [42].…”
Section: Advances In Ic In Switzerlandmentioning
confidence: 99%